The Role of Communication in Building Group Cohesiveness (Case Study of Persaudaraan Setia Hati Terate Ranting Dlingo, Bantul Regency 2023) - Amrulloh, Mazza Rois; Sari, Sovia Sitta (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: Productive activities of PSHT Ranting Dlingo members include social and humanitarian activities jointly to build group cohesion. Brotherhood is closely linked to group cohesion, and mutual assistance is a factor that affects group coherence. In building cohesion among the group members, the group is often engaged in various social activities for the sake of humanity and helping each other members who need help. Methodology: The research uses descriptive qualitative methods to describe a phenomenon in detail with a case study approach data collection through interviews and documentation. Data validity testing is done using the technique of source triangulation; data is analyzed through three stages: data reduction, data presentation, and conclusion. Results: Members who have joined for a long time have a high cohesiveness. Group communication is a forum for discussion, and supportive communication affects group cohesion. Interpersonal relationships between its members in control and orientation of problems effectively build a cohesive member. The positive activity of PSHT Ranting Dlingo is a form of productivity in building group cohesion.